A procura de si no espelho do outro: compreendendo o adolescente com características de altas habilidades/superdotação - Santos, Silvio Carlos dos (2013)
This research was mainly based on my experiences along with the students of Pedagogy and Special Education course. Such knowledge has become the focal point for me to return to the essential questioner role in the risky world of research. Therefore, I propose to investigate the adolescents construction of self-image with Characteristics of High Ability / Gifted, which was constituted in this doctoral thesis, linked to the Graduate Program in Education, in the search line LP3: Special Education, UFSM - Santa Maria Federal University -RS Brazil. To help in this clash and list some possible solutions it was outlined as general aim to investigate, through the Narcissus Myth, as one builds his/her self-image on educational relationships as a reflection on the other. To advise, it was pointed out some specific objectives, such as: understanding the conception that one has of oneself; identify as the other, from educational space he sees and reveals oneself; and finally describes how he from the (intra / inter) relationship with the reflection of the other, builds one s self-image. The participants who contributed were three teenagers, one of them a 15-year-old teenager with characteristics described previously and two others not having such attributes, besides other testimonials / memorable from this mother, other mothers from the group and other teenagers disposal here, too, as objects of study. The criteria used for selecting this target corresponded to some inclusion and exclusion insights. Related to the teenage X, 15 and his characteristics were considered the identification made by the TIP - Talent Incentive Program, developed by UFSM (Santa Maria Federal University); being within the age group of 12 to 18 years old, according to the Child and Adolescent Statute and being male, as the central character of the Narcissus Myth belongs to this genre. Moreover, the other participants should be appointed by the Teenage X and legitimized by the members who make up their (inter) personal relationships. One of them, the Teenager Y, aged 17, is part of the acquaintanceship cycle that expresses a positive attitude toward to order and proximity, and another, codenamed Z, aged 16, reflecting a negative image reflex, because he is considered an opponent for attending the same educational spaces, which will outline the adolescent self-image construction, central focus for this investigation. Therefore, to present possible solutions to the aim and the Thesis problematization it was used descriptive research with case study interpretation, because the variety and searching of nexus with the object in question. For a better data explanation, It was used the qualitative method because it gave information of reality that could not be quantified. To study the declarations and contents, it was aimed to support the narrative analysis, since the stories and reports are commonplace in the investigated participants everyday life. For the subsidies collection and recording were used instruments such: semi-structured interview, notes in the logbook or observations and recordings field. Considering the statements and records of these observations, It was chosen to make the data analysis in the course of the chapters juxtapose prominent theorists. Narcissus still roams the societies today, equivalent to the ego in its difficult struggle to be born, to firm up and strengthen. The adolescence stage is marked by conceptual confusion and loss of certain references in the meeting of equals in the world of unequals. At no time is so urgent and so hard to become one. It is at school that this teenager experiences the moment of confrontation of various conceptions of what being an adolescent is, in his parents view, himself, his peers and the professionals working in education. The study of the adolescent self-image construction compared to others in the educational space gave origin to the defense of this thesis considering it as ontologically human, central to his eternal development. Finally, educational theoricals, High Ability / Gifted, multiple intelligences, psychological theories and the Narcissus Myth will be key references for the central corpus of this Doctoral Thesis.